Abdominal apoplexy: rupture of short gastric artery after retching - Theiyallen Ambikapathi; Sentilnathan Subramaniam; Mohd Firdaus Mohd Hayati (Surgical Society of Kenya, 2022)
Abdominal apoplexy, or idiopathic spontaneous intraperitoneal hemorrhage (ISIH), is a rare but often fatal condition resulting from a variety of disease processes affecting abdominal vasculature. A 30-year-old woman presented with acute abdominal pain and breathlessness and was in class II hypovolemic shock. She had a history of multiple episodes of retching with non-bilious vomiting prior to that. Computed tomography (CT) reported a non-rotation of the gut, gross intraperitoneal free fluid with debris, and possible perforated appendicitis. Laparoscopy revealed a gross hemoperitoneum of 2.5 L, with bowel findings consistent with non-rotation of the gut, but technical difficulty in identifying the source of bleeding led to conversion to laparotomy. A ruptured short gastric artery was ascertained to be the source of bleeding and was successfully ligated. A retrospective review of the preoperative CT showed intraperitoneal free fluid with Hounsfield unit measurements of 48 and 52, suggestive of acute hemoperitoneum. ISIH is often a delayed diagnosis or missed diagnosis due to its low incidence. The presence of vomiting and abdominal pain with hypovolemic shock, especially in a young individual, should raise the suspicion of ISIH, which can be confirmed via early CT imaging to facilitate achieving hemostasis during surgery.